PENGARUH PENGGUNAAN MEDIA PETA INTERAKTIF “CAKRAWALA BUDAYA” TERHADAP HASIL BELAJAR IPAS MATERI KERAGAMAN BUDAYA DAN KEARIFAN LOKAL SISWA KELAS IV SD PERCONTOHAN 091317 P. RAYA T.A 2025/2026 - Sitopu, Ria Jelita; Nurmayani; Edizal Hatmi; Lala Jelita Ananda; Waliyul Maulana Siregar (STKIP Subang, 2026)
This study aims to investigate the effect of using the interactive map “Cakrawala Budaya” on the Social Studies (IPAS) learning outcomes of fourth-grade students at SD Percontohan 091317 Pematang Raya, Raya District, Simalungun Regency. The method used was a quasi-experimental design with a Nonequivalent Control Group Design, involving two classes: an experimental class and a control class. The sample size used in this study was 50 students, drawn using a total sampling technique. The results showed that the use of interactive maps significantly improved student learning outcomes, with the experimental group's average learning outcome reaching 86.92, while the control group's average was 76.88. Hypothesis testing using an Independent Sample t-test yielded a significant value (p < 0.001), indicating a significant positive effect of interactive maps on learning outcomes. Based on these results, it can be concluded that the use of interactive maps significantly improves the learning outcomes of fourth-grade elementary students at SD 091317 Pematang Raya.